Biomimetic pH/redox dual stimuli‐responsive zwitterionic polymer block poly(L‐histidine) micelles for intracellular delivery of doxorubicin into tumor cells. Issue 12 (13th April 2017) - John, Johnson V.; Uthaman, Saji; Augustine, Rimesh; Manickavasagam Lekshmi, Kamali; Park, In‐Kyu; Kim, Il
ABSTRACT: A series of pH/redox dual stimuli‐responsive poly(2‐methacryloyloxyethyl phosphorylcholine)25 ‐ block ‐poly(l ‐histidine) n (p[MPC])25 ‐ b ‐p[His]n, n  = 20, 35, 50, and 75) copolymers consisting of a pH‐responsive p(His) n block and a biocompatible phospholipid analog p(MPC) block connected by a redox‐responsive disulfide linker have been synthesized. The block copolymers are self‐assembled into uniform micelles (∼100 nm) in which doxorubicin (Dox) is efficiently encapsulated. The in vitro release profile shows an enhanced release of Dox at low pH (5.0) in 10 mM glutathione (GSH). The in vitro cell viability assays performed using various cell lines show that the blank hybrid micelles have no acute or intrinsic toxicity. A pH‐dependent cytotoxicity is observed with the Dox‐loaded micelles, especially at pH 5.0. Moreover, confocal microscopy images and flow cytometry results show the pH‐dependent cellular uptake of Dox‐loaded micelles. Therefore, the Dox‐loaded micelles can be considered a good candidate for cancer therapy. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 2061–2070 Abstract : A series of synthetic polymer/polypeptide block copolymers consisting of a pH‐responsive polypeptide unit and a biocompatible and soluble zwitterionic polymer unit are designed. Both units are connected by a redox‐responsive disulfide linkers. The new block copolymers self‐assemble to form uniform micelles around 100 nm in size, and they show efficient pH/redox dual‐stimuli responsive drug delivery into tumor cells.